The Implementation of the Istanbul Convention in the #Metoo Era: The Services Available to Immigrant Women in Iceland - Telma Marisa Ojeda Velez 1980- (2022)
In 2011, the Council of Europe adopted the Convention on preventing and combating violence against women and domestic violence (Istanbul Convention). As a signatory, Iceland agreed to secure the rights of victims of gender-based violence without any discrimination. According to Article 15 of the Convention, “appropriate training for relevant professionals should be ensured to prevent secondary victimization and parties shall encourage co-ordinated multi-agency co-operation training to allow a proper handling of referrals in cases of violence”. In addition, Article 20 of the Convention states that “necessary measures should be taken to ensure that victims have access to relevant and needed services that facilitate their recovery”. The narratives published in January 2018, at the height of the #metoo movement in Iceland, revealed that immigrant women who experience intimate partner violence (IPV) are not provided with adequate services in accordance with either Article 15 or 20 of the Convention. The narratives detail levels of violence that intersect with race and ethnicity, indicating potential structural and systemic issues within Icelandic society. Using an intersectional lens premised on Articles 15 and 20, this paper analyses the content of 14 narratives and eight stakeholder interviews with service providers. Results indicate that services available to immigrant women fail to accommodate their needs in a culturally appropriate way, and the staff lack sufficient multicultural training, perpetuating further victimisation through structural violence. This paper brings forth an understanding whether or not services provide culturally relevant care according to the Istanbul Convention for immigrant women who experience gender-based violence. Rannís and Jafnréttisjóður Íslands